Epidemiological characterization of congenital heart disease at different altitudes in Ecuador: a four-year retrospective study in a pediatric referral hospital - Juan S. Izquierdo-Condoy; Fabian D. Arias-Rodríguez; Walter I. Díaz-Chamba; Diego A. Mena-Noroña; Lizbeth Cueva Toaquiza; Beanjuly Espín-Sambache; Emilia J. Valdivieso-Andrade; Amanda Cangas-Isacaz; Susana García-Cañarte; Mario Rubio-Niera; Esteban Ortiz-Prado (Frontiers in Public Health)
BackgroundCongenital heart disease (CHD) is one of the main causes of hospital admissions and infant mortality, especially in developing regions.ObjectivesThis study aims to describe the epidemiological and clinical features of CHD in pediatric patients, from one of the largest tertiary-level national referral pediatric hospitals in Ecuador.Materials and methodsAn epidemiological, retrospective cohort study was conducted among patients with CHD who were hospitalized at “Hospital Baca Ortiz” between January 2019 to December 2022 in Quito, Ecuador.ResultsA total of 1,000 pediatric patient medical records were reviewed from 2019 to 2022. Among these patients, 56.0% were female, and 65.2% resided at high altitudes (2,500–3,500 m). Most cases (71.4%) were acyanotic CHD, with patent ductus arteriosus being the most prevalent (48.7%). Among cyanotic CHD, Tetralogy of Fallot was predominant (28.1%). Mortality was observed in 5.3% of patients, with a higher rate among acyanotic CHD (p < 0.001).ConclusionMost cases of CHD were of the acyanotic type, predominantly affecting female patients. Although most cases occurred in children living above 2,500 meters, no clear influence of altitude on specific types of CHD was found. While mortality related to CHD was low, the burden of disability from these conditions was significant among patients with acyanotic CHD.